Mothers’ parenting of adolescents in the VUCA era: a phenomenological analysis - Handayani, Arri; Dhyah Yulianti, Padmi; Menarianti, Ika (Jurnal Konseling dan Pendidikan, 2025)
In the VUCA era (volatility, uncertainty, complexity, ambiguity), mothers must adjust their parenting without neglecting family values. This study investigated mothers’ experiences in guiding adolescents during the VUCA era and identified their adaptive strategies based on Duvall’s family development theory. This qualitative phenomenological design involved three mothers as participants taken with purposive sampling, with data collected through interviews, observations, and focus group discussions (FGDs). The researcher analyzed the data using Interpretative Phenomenological Analysis. The findings revealed five main themes indicating that mothers’ interpretations of their parenting roles influence their experiences, psychological stress, expectations, and the parenting strategies they adopt. Mothers’ roles in parenting adolescents have shifted from traditional approaches to more modern, adaptive, and holistic models. In adapting to these dynamics, mothers involved multiple components, including themselves, their adolescent children, their husbands, and the wider community. The findings also demonstrated the expansion of Duvall's family development theory to incorporate new dynamics, particularly those fuelled by technological advancements. Support programs that enhance adolescents' emotional regulation skills can implement this research in school counseling services. For community-based applications, a systems approach involving fathers and other family members can be used, along with digital parenting platforms such as e-parenting.id for education and counseling. Counselors can also provide training and support to address parenting-related stress among mothers and offer family counseling to improve family well-being.